Effect of Intravitreal Bevacizumab on Retrobulbar Blood Flow of Patients with Diabetic Macular Edema. Issue 6 (December 2015) - Örnek, Nurgül; Inal, Mikail; Erbahceci, Inci Elif; Oğurel, Tevfik; Örnek, Kemal
Purpose: To determine the effect of intravitreal bevacizumab on retrobulbar blood flow of patients with diabetic macular edema. Methods: Peak systolic velocity, end-diastolic velocity, resistance, and pulsatility indices of central retinal artery (CRA), nasal posterior ciliary artery (NPCA), temporal posterior ciliary artery (TPCA), and ophthalmic artery (OA) were assessed by color Doppler ultrasonography in injected and uninjected eyes of 37 patients at baseline and at day 1 and day 7 after the injection. Results: At day 1 after the injection, peak systolic and end diastolic velocities of the CRA and NPCA in the injected eyes and peak systolic velocity of NPCA in the uninjected eyes decreased significantly (p<0.05, p = 0.025, respectively). Peak systolic and end diastolic velocities were not significantly different in the injected and uninjected eyes at day 7 after the injection (p>0.05). In the injected eyes, there was no significant change in resistance and pulsatility indices (p>0.05), but a decrease in resistance index of NPCA and resistance and pulsatility indices of TPCA occurred in uninjected eyes at day 7 after the injection (p = 0.016, p = 0.023, and p = 0.025, respectively). Conclusions: Intravitreal bevacizumab affects retrobulbar blood flow in injected and uninjected eyes of patients with diabetic macular edema.